Pathogenic mechanisms underlying adverse reactions induced by intravenous administration of snake antivenoms - León Montero, Guillermo (2013)
Snake antivenoms are formulations of immunoglobulins, or immunoglobulin fragments, purified from the plasma of animals immunized with snake venoms. Their therapeutic success lies in their ability to mitigate the progress of toxic effects induced by snake venom components, when administered intravenously. However, due to diverse factors, such as deficient manufacturing practices, physicochemical characteristics of formulations, or inherent properties of heterologous immunoglobulins, antivenoms can induce undesirable adverse reactions. Based on the time lapse between antivenom administration and the onset of clinical manifestations, the World Health Organization has classified these adverse reactions as: 1 – Early reactions, if they occur within the first hours after antivenom infusion, or 2 – late reactions, when occurring between 5 and 20 days after treatment. While all late reactions are mediated by IgM or IgG antibodies raised in the patient against antivenom proteins, and the consequent formation of immune complexes, several mechanisms may be responsible for the early reactions, such as pyrogenic reactions, IgE-mediated reactions, or non IgE-mediated reactions. This work reviews the hypotheses that have been proposed to explain the mechanisms involved in these adverse reactions to antivenoms. The understanding of these pathogenic mechanisms is necessary for the development of safer products and for the improvement of snakebite envenomation treatment.